Evolution of Federal Transportation Policy and Finance in the USA in the Twentieth Century - Yulia LEONTYEVA; Igor MAYBUROV (Communications of International Proceedings, 2020)
This research, especially on the financial aspects, will be of particular interest in Russia, which, half a century after the USA, has faced the need to develop a rational transport policy, including the choice of adequate fiscal instruments for its implementation. The aim of this article is to trace the history of American twentieth-century transportation policy-making and financing. This study relies on methods of historical research and logical analysis. The general trend that determined the US transport policy in the twentieth century - the primacy of the automobile - remained more or less stable throughout the given period. However, the creation of a trust fund for more efficient and better targeted financing of road construction can definitely be regarded as a positive experience to learn from. Throughout the twentieth century, in their choice of priorities, American policy-makers almost always focused on the car as the dominant mode of travel. The priority goal of the transport policy was to provide traffic congestion relief. Unsurprisingly, this problem was addressed through heavy investment in road space expansion. To summarize the above analysis, we can point out the following three periods: 1920-1960s – Mass automobilization, conditions highly conducive to car use; 1960-1990s – Growing car dependence, suburban sprawl, conditions conducive to car use; 1990s – Development of multi-modal transportation, growing constraints on car use.
Keywords: Transport Policy; Transport Taxes; Trust Fund; Conducive to Car Use.